Light Localization and Principal Mode Propagation in Optical Fibers - Nolan, Daniel A.; Nguyen, Dan T. (Frontiers in Physics, 2021)
The capacity of optical fiber communications has grown exponentially since its implementation decades ago. Optical fiber amplifiers, wavelength division multiplexing, and coherent communications have all enabled discontinuous growth. Space division multiplexing is proposed as the next discontinuity. Here tens of modes rather than a single mode are utilized in the transmission. Random scattering due to index fluctuations within the optical fiber cause coupling among the modal channels thereby degrading signal transmission. Principal mode transmission overcomes this limitation. Here a set of modes arrive localized at the fiber output unscattered. We review this methodology as it relates to optical communication capacity, but also as it relates to light localization. We also review the characterization of these modes both theoretically and experimentally.